PEMANFAATAN MEDIA PAPAN PINTAR BERBAHAN DAUR ULANG DALAM MENINGKATKAN KETERLIBATAN BELAJAR SISWA KELAS V SEKOLAH DASAR - Rosanti, Atik; Fauziah Rahmah, Annisa; Nur Farida, Siti; Mu`tiqotul Azizah, Muti; Nur Fadillah, Miranda; Delal; Elma Diani Rum`azizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted based on the researcher’s direct experience during the PLP 2 program at SDN 1 Darma, where observations were carried out on the use of recycled smart board learning media developed by a fifth-grade homeroom teacher. The media was applied as an alternative instructional variation in classroom learning and received a positive response from students. Early observations showed that students demonstrated higher levels of engagement when learning activities incorporated smart board media compared to learning that relied solely on textbooks. Based on these conditions, this study aims to examine how the use of recycled smart board media contributes to supporting student engagement in fifth-grade elementary classrooms. This research employed a qualitative descriptive design involving fifth-grade students at SDN 1 Darma. Data were obtained through classroom observations, interviews with teachers and students, as well as documentation of learning activities. The data analysis process consisted of data reduction, data presentation, and conclusion drawing. The results indicate that the application of smart board media fostered a more interactive learning atmosphere, encouraged active student participation, and increased students’ confidence during the learning process. In addition, the media helped teachers deliver learning materials in a more concrete manner that aligns with the characteristics of elementary school students. Therefore, recycled smart board media can be regarded as an effective learning practice to enhance student engagement at the elementary education level.